(untitled) (European journal of volunteering and community-based projects, 2021)
The Natural killer (NK) cells’ ability to destroy cancerous cells is predominantly focused on the activation of the co-stimulatory and natural killer group two with receptor of member-D also called NKGD2/NKG2D. These identifies ligands that are MHC-Class1 structural homologs like that of the UL16 protein-binding type 2. The ULBP2 has been shown to mediate-natural resistance against the tumors mechanism in the condition of in-vitro, in-vivo, making it a possible target for producing the immune-therapeutic drugs for the diagnosis of the cancers and certain other viral diseases. In this present research, we created a stable and high-quality 3-D structure of the ULBP-2 protein through SWISS-Model also visualized by using UCSF-Chimera Tool. Moreover, the ULBP2 protein was prognosticated to be acts as antigenic, 11-discontinuous-B-Cell epitopes, 05 ULBP2 proteins antibody-based epitopes, and possible predicted the top hits of six linear B-cell epitopes. The ULBP2 protein carried seven cytotoxic-T lymphocytes (CTLs), two helper-T lymphocytes (HTLs), the LGKKLNVTTAWAQN is a promiscuous epitope MHC bounded to the T cells and with LRDIQLENY highest antigen scores in MHC molecule. Finally, the promising epitopes that could be successful in producing B-cell and T-cell mediated immunity against the required immune reaction to tumorigenesis were expected.